2016
DOI: 10.1007/s11663-016-0685-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Complex Sulfide Inclusion Formation in Ca-Treated Al-Killed Structural Steel

Abstract: Controlling the morphology of the sulfide inclusion is of vital importance in enhancing the properties of structural steel. Long strip-shaped sulfides in hot-rolled steel can spherize when, instead of the inclusion of pure single-phase MnS, the guest is a complex sulfide, such as an oxide-sulfide duplex and a solid-solution sulfide particle. In this study, the inclusions in a commercial rolled structural steel were investigated. Spherical and elongated oxide-sulfide duplex as well as single-phase (Mn,Ca)S soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
(20 reference statements)
1
25
0
1
Order By: Relevance
“…Normally, calcium addition is an effective way to alter the morphology and dispersion of non-metallic inclusions in the continuous casting process or in ingots. Calcium treatment is normally applied in Al-deoxidized steels to alter the solid alumina inclusions into liquid ones [11][12][13] which effortlessly pass through without spout impediment. In the current operations, the inclusions modification proficiency using Ca is usually not high; the surplus Ca may cause the development of high temperature stable inclusions such as CaS and Ca•Al 12 O 19 , leading to spout impediment [2,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, calcium addition is an effective way to alter the morphology and dispersion of non-metallic inclusions in the continuous casting process or in ingots. Calcium treatment is normally applied in Al-deoxidized steels to alter the solid alumina inclusions into liquid ones [11][12][13] which effortlessly pass through without spout impediment. In the current operations, the inclusions modification proficiency using Ca is usually not high; the surplus Ca may cause the development of high temperature stable inclusions such as CaS and Ca•Al 12 O 19 , leading to spout impediment [2,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…During the production of Al-killed steels, alumina inclusions were modified to calcium aluminate by Ca treatment or slag-steel interaction [1][2][3] to reduce the adverse effect on the steel quality caused by the nozzle clogging or poor deformability of inclusions. [4][5][6][7] The formation of CaS occurred in both liquid [8,9] and solid steels, [10,11] resulting in defects of steel products such as pitting. [12] Shin et al verified the participation of Al during the formation of CaS in the liquid steel following the reaction of 2[Al] þ 3[S] þ 3(CaO) ¼ (Al 2 O 3 ) þ 3(CaS).…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic calculations also have been performed to predict the type of calcium aluminates and reliable stability phase diagram of various calcium aluminates were obtained [13]. However, the reactions in the molten steel are complex and inclusions containing CaS would form as the existence of S and CaS inclusions are undeformable [14,15]. Verma and Pistorius et al [16,17] investigated the composition evolution of inclusions in liquid steel modified by calcium and found that CaS may form as an intermediate reaction product, which can subsequently react with Al 2 O 3 to form calcium aluminates as reaction [1].…”
Section: Introductionmentioning
confidence: 99%
“…Oxide-sulfide duplex inclusions were also detected in the steel containing certain Mn, such as semi-free-cutting steels [26,27]. MnS precipitating during cooling and solidification can dissolve with CaS and generate a solid of (Mn, Ca) S [14]. The modification of inclusions by calcium treatment is more complex in this steel containing Al, Mn, and S. It is proposed Al 2 O 3 -CaS inclusions had a detrimental effect on the magnetic properties of a Ca-treated non-oriented electrical steel [28], but the complex inclusions mCaO.nAl 2 O 3 -(Mn, Ca) S with duplex phase can be a protective film on the rack face, which improves the durability of the tool [29].…”
Section: Introductionmentioning
confidence: 99%